PROFIL MINAT BACA DAN KEMAMPUAN MEMBACA MELALUI MEDIA BIG BOOK BERBASIS LITERASI UNTUK MENINGKATKAN KEMAMPUAN BERKOMUNIKASI SISWA KELAS I SEKOLAH DASAR - Indah Trissetyowati; Agus Wardhono; Fera Dwidarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Basic literacy in early elementary school is the foundation for developing students' reading and communication skills. Observations at Grade I of UPT SD Negeri Sidonganti 1, Kerek District, Tuban Regency revealed that students' reading interest, beginning reading ability, and oral communication skills were still low. This study aims to describe the profile of reading interest, reading ability, and communication skills of Grade I students through the application of literacy-based Big Book media. A qualitative descriptive approach was used. The research subjects were 15 Grade I students consisting of 8 male and 7 female students. Data collection employed observation, interviews, and documentation. Data analysis was conducted using Miles and Huberman's interactive model through data reduction, data display, and conclusion drawing. The results show that the use of literacy-based Big Book media effectively improved students' reading interest, enhanced beginning reading skills, and encouraged students to be more active and confident in oral communication. Big Book creates an interactive, enjoyable, and contextual learning atmosphere that supports the optimal development of student literacy and communication. The role of the teacher as a facilitator is a key factor in optimizing the use of Big Book as a literacy and communication media in early grade learning.